Liposomal drug delivery to manage nontuberculous mycobacterial pulmonary disease and other chronic lung infections. (21st July 2021) - Chalmers, James D.; van Ingen, Jakko; van der Laan, Roald; Herrmann, Jean-Louis
Nontuberculous mycobacterial (NTM) pulmonary disease is a chronic respiratory infection associated with declining lung function, radiological deterioration and significantly increased morbidity and mortality. Patients often have underlying lung conditions, particularly bronchiectasis and COPD. NTM pulmonary disease is difficult to treat because mycobacteria can evade host defences and antimicrobial therapy through extracellular persistence in biofilms and sequestration into macrophages. Management of NTM pulmonary disease remains challenging and outcomes are often poor, partly due to limited penetration of antibiotics into intracellular spaces and biofilms. Efficient drug delivery to the site of infection is therefore a key objective of treatment, but there is high variability in lung penetration by antibiotics. Inhalation is the most direct route of delivery and has demonstrated increased efficacy of antibiotics like amikacin compared with systemic administration. Liposomes are small, artificial, enclosed spherical vesicles, in which drug molecules can be encapsulated to provide controlled release, with potentially improved pharmacokinetics and reduced toxicity. They are especially useful for drugs where penetration of cell membranes is essential. Inhaled delivery of liposomal drug solutions can therefore facilitate direct access to macrophages in the lung where the infecting NTM may reside. A range of liposomal drugs are currently being evaluated in respiratory diseases. Liposome-encapsulated antibiotics can optimise respiratory disease treatment. Amikacin liposomal inhalation suspension is effective in nontuberculous mycobacterial pulmonary disease that has failed to convert following oral guideline-based therapy. https://bit.ly/3f3ixIu